A flux-cored welding wire for high-energy-line welding and its preparation method and application
By introducing CaF2-TiO2 smelting flux and Ta into the welding wire, the generation of needle-shaped ferrite is promoted, and the problem of deterioration of the mechanical properties of the welding joints in large heat input welding is solved, and high mechanical properties and safety and reliability are achieved under the conditions of super-large wire energy welding.
Patent Information
- Application Number
- CN202411233697.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-04
AI Technical Summary
During the high heat input welding process, the increase in the temperature of the weld joint causes the weld metal grain to coarse and deteriorate the mechanical properties. Especially under the conditions of super large line energy welding, it is difficult for the prior art to ensure the high mechanical properties and safety and reliability of the welded joints.
A flux-core welding wire is used, and its flux-core is composed of components such as C, Al, Si, Mn, Ni, Ti, Mo, Ta and CaF2-TiO2 smelting flux. Through the introduction of CaF2-TiO2 smelting flux and the addition of Ta, the generation of needle-shaped ferrite is promoted and the strength and toughness of weld metal are improved.
Under the input of EGW's super-large line energy heat, the weld metal of the flux-core welding wire maintains strength matching the base material and has a high low-temperature impact toughness, and its mechanical properties are much higher than the required value, including the tensile strength, yield strength, hardness and impact absorption energy.
Smart Images

Figure BDA0005027074940000061 
Figure BDA0005027074940000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of welding materials, and in particular relates to a flux-cored welding wire for large-line energy welding and a preparation method and application thereof. Background Art
[0002] In recent years, in the field of large-scale equipment manufacturing such as shipbuilding, large oil storage tanks, high-rise buildings and marine engineering, as steel components become larger and larger in span, welding as an important part of secondary processing has received more and more attention. In order to reduce welding hours, improve welding construction efficiency, and reduce the cost of component welding and manufacturing, high heat input welding methods such as gas-electric vertical welding, submerged arc welding, and electroslag welding are widely used. However, during the high heat input welding process, the temperature of the weld joint increases, the residence time of the weld metal at high temperature increases, and the cooling rate slows down, resulting in the coarsening of the weld heat affected zone (HAZ) and the weld metal grains, and the serious deterioration of the mechanical properties, which has a strong negative impact on the safe use of the components. In particular, with the development of industries such as construction and shipbuilding towards large-scale and high-efficiency, higher line energy welding technology is urgently needed, and the steel structure is required to still have high mechanical properties under ultra-large line energy welding conditions of more than 500kJ / cm to ensure the safety and reliability of the engineering structure.
[0003] It is in this application demand background that Japanese scholars proposed in the 1990s to use fine dispersed inclusion particles in steel as particles to hinder the growth of γ grains and induce the nucleation of intracrystalline acicular ferrite (AF), on the one hand to pin the original γ grain boundary, and on the other hand to induce the formation of AF to divide and refine the original γ grains, thereby refining the structure. In the past few decades, the traditional method to improve the toughness of welded joints is to disperse fine TiN particles to pin the γ boundary to prevent the growth of γ grains. However, due to the high solubility of TiN in steel at high temperature, it is very easy to dissolve during the welding thermal cycle, especially under ultra-high line energy welding conditions, the peak temperature of the welding thermal cycle is higher, and these nitrides are more soluble, thereby greatly reducing their pinning effect on the γ grain boundary. In this context, many scholars continue to explore the introduction of new non-metallic inclusions in steel to improve the mechanical properties of welded joints. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a flux-cored welding wire.
[0005] A second object of the present invention is to provide a method for preparing a flux-cored welding wire.
[0006] A third object of the present invention is to provide a flux-cored welding wire for use in the field of welding.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a flux-cored welding wire, comprising an outer skin and a flux core, wherein the flux core is filled inside the outer skin; the flux core is composed of the following components in mass percentage: C 0.48-0.78%, Al 0.72-0.84%, Si 1.50-1.62%, Mn 10.20-11.40%, Ni 2.10-2.46%, Ti 1.14-1.26%, Mo1.08-1.14%, Ta 0.06-1.48%, CaF2-TiO2 smelting flux 5-7%, and Fe as the balance.
[0009] Preferably, the CaF2-TiO2 smelting flux in the flux core is prepared by a preparation method comprising the following steps:
[0010] The CaF2 and TiO2 are mixed and smelted at a temperature not lower than 1550°C to obtain a smelting product; the smelting product is quenched with water and calcined at 700-900°C for 3-5 hours, crushed and sieved to obtain the CaF2-TiO2 smelting flux. The calcination step is used to fully consume the carbon element in the smelting flux to avoid the influence of the carbon element on the flux-cored wire.
[0011] Preferably, the smelting step is performed in a graphite crucible.
[0012] Preferably, the smelting and holding time is 8 to 12 minutes.
[0013] Preferably, the particle size of the CaF2-TiO2 smelting flux is 10-40 meshes.
[0014] Preferably, the CaF2-TiO2 smelting flux in the flux core is prepared by a preparation method comprising the following steps:
[0015] Put CaF2 and TiO2 into a mixing device and mix them evenly, then put them in a graphite crucible, melt them at a temperature not lower than 1550°C, keep them warm for 10 minutes, and then quench them with water to obtain a semi-finished product, and roast the semi-finished product at 700-900°C for 3-5h to fully consume the carbon element in the flux, then crush and sieve them to obtain particles with a particle size of 10-40 mesh, which is the CaF2-TiO2 type melting flux.
[0016] Preferably, the filling rate of the flux core in the flux cored welding wire is 20-30%. The filling rate is the ratio of the mass of the flux core to the sum of the mass of the flux core and the outer sheath.
[0017] Preferably, the outer skin is H08A steel, which is low-carbon low-alloy steel.
[0018] Preferably, the particle size of the drug core is ≤80 mesh.
[0019] Preferably, in the CaF2-TiO2 melting flux, the mass percentage of CaF2 is 25-60%, and the mass percentage of TiO2 is 40-75%. In the present invention, the CaF2-TiO2 melting flux can be used as a slag-forming agent to protect the molten pool and stabilize the arc during welding.
[0020] Preferably, the flux-cored welding wire is suitable for ultra-large energy input welding of 400-800 kJ / cm; further preferably, preferably, the flux-cored welding wire is suitable for ultra-large energy input welding of 600-800 kJ / cm.
[0021] Preferably, the diameter of the flux-cored welding wire is 1.6 mm.
[0022] The second aspect of the present invention provides a method for preparing the flux-cored welding wire provided by the first aspect of the present invention, comprising the following steps:
[0023] The raw materials of the flux core are mixed and filled into the outer skin, and then cold-bent, sealed, drawn and reduced in diameter to obtain the flux-cored welding wire.
[0024] Preferably, the method for preparing the flux-cored welding wire comprises the following steps:
[0025] Drying and mixing the raw materials of the drug core to obtain a drug core mixed powder;
[0026] The outer skin is rolled into a U shape, the flux core mixed powder is filled into the outer skin, and then the outer skin is cold-bent, sealed, and drawn to reduce the diameter, so as to obtain the flux core welding wire.
[0027] Preferably, the drying temperature is 90-130°C.
[0028] Preferably, the drying time is 4 to 24 hours.
[0029] Preferably, the mixing is performed using a Y-type powder mixer.
[0030] Preferably, the mixing time is 30 to 40 minutes.
[0031] Preferably, the skin needs to be washed and dried before use.
[0032] The third aspect of the present invention provides application of the flux-cored welding wire provided by the first aspect of the present invention in the field of welding.
[0033] The beneficial effect of the present invention is that the flux-cored welding wire in the present invention still maintains strength matching that of the base material and high low-temperature impact toughness under EGW ultra-large linear energy heat input (for example, greater than 600 kJ / cm), and the mechanical properties are much higher than the required values, specifically: tensile strength greater than 560 MPa, yield strength greater than 440 MPa, elongation after fracture greater than 20%, and hardness greater than 180 HV.
[0034] CaF2-TiO2 melting flux is added to the flux-cored welding wire of the present invention, which can make the weld have good formability and excellent arc stability. At the same time, TiO2 may decompose at high temperature, increase the Ti and O content in the weld metal, and promote the formation of Ti-containing inclusions, which can effectively induce the nucleation of acicular ferrite. In addition, the introduction of Ta increases the precipitation amount of MX-type carbides, plays a significant dispersion strengthening effect, and greatly improves the strength of the weld metal. At the same time, Ta has a high affinity with O, and it is very easy to form Ta2O5 during the welding process. This oxide has the characteristics of high melting point and high hardness, and can be used as an effective nucleation point for acicular ferrite. Ta is a ferrite stabilizing element. The addition of Ta increases the temperature of austenite to ferrite transformation in the weld, which is beneficial to enhance the phase transformation driving force of ferrite transformation and promote the nucleation of acicular ferrite on the surface of Ta2O5. As a result, the weld metal still maintains strength matching that of the base material and high low-temperature impact toughness under EGW ultra-large line energy heat input (greater than 600 kJ / cm), and the mechanical properties are much higher than the required values. DETAILED DESCRIPTION
[0035] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0036] In the CaF2-TiO2 smelting flux used in the embodiment of the present invention, the mass percentage of CaF2 is 50%, and the mass percentage of TiO2 is 50%. The preparation method thereof is as follows:
[0037] According to the formula ratio, sufficient amount of CaF2 and TiO2 are weighed and put into a mixing equipment to mix evenly, then placed in a graphite crucible, smelted at 1550°C, kept warm for 10 minutes, and then water quenched to obtain a semi-finished product, which is calcined at 800°C for 4 hours to fully consume the carbon element in the flux, and then crushed and sieved to obtain particles with a particle size of 10-40 mesh, which is the CaF2-TiO2 type molten flux.
[0038] Example 1
[0039] This example provides a flux-cored welding wire for high-energy line welding, which consists of two parts: an outer skin and a flux core. The outer skin is an H08A steel strip with a thickness of 0.6 mm and a width of 12 mm. Taking the total mass percentage of the flux core as 100%, the flux core is composed of the following components in mass percentage: C 0.48%, Al 0.78%, Mn 10.5%, Si 1.55%, Ni 2.10%, Mo1.08%, Ti 1.14%, Ta 0.06%, CaF2-TiO2 molten flux 5%, and the rest is Fe.
[0040] The flux-cored welding wire for high-energy line welding in this example is prepared by a preparation method comprising the following steps:
[0041] (1) selecting powder with a particle size of less than 80 mesh as raw material according to the chemical composition of the core powder, placing the mixed powder in a drying furnace at 100° C. for 4 h for drying according to the above component ratio, and then placing it in a Y-type powder mixer for mixing for 35 min to obtain a uniformly mixed core powder;
[0042] (2) After washing, drying and cooling, the H08A steel strip is rolled into a U shape using a forming roller, and then the flux core powder obtained in step (1) is filled into the U-shaped steel strip, and the flux core filling rate is controlled to be 25%. Subsequently, a flux cored welding wire with a diameter of 1.6 mm is prepared by cold bending, sealing and multiple drawing and reducing.
[0043] Example 2
[0044] This example provides a flux-cored welding wire for high-line energy welding, which consists of two parts: an outer skin and a flux core. The outer skin is an H08A steel strip with a thickness of 0.6 mm and a width of 12 mm. Based on the total mass percentage of the flux core being 100%, the flux core is composed of the following components in mass percentage: C 0.55%, Al 0.74%, Mn 10.60%, Si 1.50%, Ni 2.34%, Mo1.11%, Ti 1.15%, Ta 0.09%, CaF2-TiO2 molten flux 5%, and the remainder being Fe.
[0045] The flux-cored welding wire for high-energy line welding in this example is prepared by a preparation method comprising the following steps:
[0046] (1) selecting powder with a particle size of less than 80 mesh as raw material according to the chemical composition of the core powder, placing the mixed powder in a drying furnace at 100° C. for 4 h for drying according to the above component ratio, and then placing it in a Y-type powder mixer for mixing for 35 min to obtain a uniformly mixed core powder;
[0047] (2) After washing, drying and cooling, the H08A steel strip is rolled into a U shape using a forming roller, and then the flux core powder obtained in step (1) is filled into the U-shaped steel strip, and the flux core filling rate is controlled to be 25%. Subsequently, a flux cored welding wire with a diameter of 1.6 mm is prepared by cold bending, sealing and multiple drawing and reducing.
[0048] Example 3
[0049] This example provides a flux-cored welding wire for high-line energy welding, which consists of two parts: an outer skin and a flux core. The outer skin is an H08A steel strip with a thickness of 0.6 mm and a width of 12 mm. Based on the total mass percentage of the flux core being 100%, the flux core is composed of the following components in mass percentage: C 0.68%, Al 0.72%, Mn 10.2%, Si 1.52%, Ni 2.44%, Mo1.08%, Ti 1.26%, Ta 0.13%, CaF2-TiO2 molten flux 6%, and the remainder being Fe.
[0050] The flux-cored welding wire for high-energy line welding in this example is prepared by a preparation method comprising the following steps:
[0051] (1) selecting powder with a particle size of less than 80 mesh as raw material according to the chemical composition of the core powder, placing the mixed powder in a drying furnace at 100° C. for 4 h for drying according to the above component ratio, and then placing it in a Y-type powder mixer for mixing for 35 min to obtain a uniformly mixed core powder;
[0052] (2) After washing, drying and cooling, the H08A steel strip is rolled into a U shape using a forming roller, and then the flux core powder obtained in step (1) is filled into the U-shaped steel strip, and the flux core filling rate is controlled to be 25%. Subsequently, a flux cored welding wire with a diameter of 1.6 mm is prepared by cold bending, sealing and multiple drawing and reducing.
[0053] Example 4
[0054] This example provides a flux-cored welding wire for high-energy line welding, which consists of two parts: an outer skin and a flux core. The outer skin is an H08A steel strip with a thickness of 0.6 mm and a width of 12 mm. Based on the total mass percentage of the flux core being 100%, the flux core is composed of the following components in mass percentage: C 0.57%, Al 0.73%, Mn 11.40%, Si 1.53%, Ni 2.46%, Mo1.14%, Ti 1.25%, Ta 0.768%, CaF2-TiO2 molten flux 6%, and the rest is Fe.
[0055] The flux-cored welding wire for high-energy line welding in this example is prepared by a preparation method comprising the following steps:
[0056] (1) selecting powder with a particle size of less than 80 mesh as raw material according to the chemical composition of the core powder, placing the mixed powder in a drying furnace at 100° C. for 4 h for drying according to the above component ratio, and then placing it in a Y-type powder mixer for mixing for 35 min to obtain a uniformly mixed core powder;
[0057] (2) After washing, drying and cooling, the H08A steel strip is rolled into a U shape using a forming roller, and then the flux core powder obtained in step (1) is filled into the U-shaped steel strip, and the flux core filling rate is controlled to be 25%. Subsequently, a flux cored welding wire with a diameter of 1.6 mm is prepared by cold bending, sealing and multiple drawing and reducing.
[0058] Example 5
[0059] This example provides a flux-cored welding wire for high-energy line welding, which consists of two parts: an outer skin and a flux core. The outer skin is an H08A steel strip with a thickness of 0.6 mm and a width of 12 mm. Based on the total mass percentage of the flux core being 100%, the flux core is composed of the following components in mass percentage: C 0.78%, Al 0.84%, Mn 10.72%, Si 1.57%, Ni 2.43%, Mo1.08%, Ti 1.21%, Ta 1.48%, CaF2-TiO2 molten flux 7%, and the remainder is Fe.
[0060] The flux-cored welding wire for high-energy line welding in this example is prepared by a preparation method comprising the following steps:
[0061] (1) selecting powder with a particle size of less than 80 mesh as raw material according to the chemical composition of the core powder, placing the mixed powder in a drying furnace at 100° C. for 4 h for drying according to the above component ratio, and then placing it in a Y-type powder mixer for mixing for 35 min to obtain a uniformly mixed core powder;
[0062] (2) After washing, drying and cooling, the H08A steel strip is rolled into a U shape using a forming roller, and then the flux core powder obtained in step (1) is filled into the U-shaped steel strip, and the flux core filling rate is controlled to be 25%. Subsequently, a flux cored welding wire with a diameter of 1.6 mm is prepared by cold bending, sealing and multiple drawing and reducing.
[0063] Comparative Example 1
[0064] This example provides a flux-cored welding wire, which consists of an outer skin and a flux core. The outer skin is an H08A steel strip with a thickness of 0.6 mm and a width of 12 mm. The flux core does not contain Ta. Based on the total mass percentage of the flux core being 100%, the flux core is composed of the following components in mass percentage: C 0.78%, Al 0.82%, Mn 11.2%, Si 1.59%, Ni 2.42%, Mo 1.13%, Ti 1.22%, CaF2-TiO2 molten flux 7%, and the remainder is Fe.
[0065] The flux-cored welding wire in this example is prepared by a preparation method comprising the following steps:
[0066] (1) selecting powder with a particle size of less than 80 mesh as raw material according to the chemical composition of the core powder, placing the mixed powder in a drying furnace at 100° C. for 4 h for drying according to the above component ratio, and then placing it in a Y-type powder mixer for mixing for 35 min to obtain a uniformly mixed core powder;
[0067] (2) After washing, drying and cooling, the H08A steel strip is rolled into a U shape using a forming roller, and then the flux core powder obtained in step (1) is filled into the U-shaped steel strip, and the flux core filling rate is controlled to be 25%. Subsequently, a flux cored welding wire with a diameter of 1.6 mm is prepared by cold bending, sealing and multiple drawing and reducing.
[0068] The flux-cored welding wires in Examples 1 to 5 and Comparative Example 1 can be butt-welded using the following process, specifically:
[0069] The ultra-large energy line welding method adopts double-wire vertical EGW, and the groove form of the parent material is designed as a single-sided V-shaped groove. The flux-cored welding wires in Examples 1 to 5 and Comparative Example 1 are respectively used to perform double-wire ultra-large energy line welding on 60mm H08A steel, wherein the groove angle is 20°, the gap is 7mm, and the blunt edge is a 0-1mm groove. The dry extension length of the two welding wires is 40mm, the welding gun angle is 6° to 10°, the distance from the rear wire to the pad is 23mm, and the spacing between the two welding wires is 17mm. The welding process parameters are: the rear wire is a DC positive connection method, fixed without swinging, the current is 526.7-554.2A, and the voltage is 47.6-50.9V; the front wire is a DC reverse connection method, the swing width is 15-20mm, the current is 531.6-564.7A, and the voltage is 49.5-51.3; the shielding gas is CO2, and the speed is 30-60mm·min -1 , heat input is 602.4~627.3kJ·cm -1 .
[0070] After welding according to the above process, performance tests were performed on the weld positions of the welds, where the hardness test was performed using a Vickers hardness tester; the tensile performance test method referred to GB / T 2652-2022 "Destructive test on metal material welds - Longitudinal tensile test of fusion welded joint weld metal"; the impact performance test method referred to GB / T 2650-2022 "Destructive test on metal material welds - Impact test", and the impact test was performed on an Instron Dynatup 9200 series drop hammer impact testing machine with an energy range of 25-1603J and a maximum impact rate of 20m / s. The weld performance test results after welding with the flux-cored wire in Examples 1 to 5 and Comparative Example 1 measured according to the above test method are shown in Table 1 below.
[0071] Table 1 Weld performance test results after flux-cored wire welding
[0072]
[0073]
[0074] It can be seen from Table 1 that Ta is added to the flux-cored wires in Examples 1 to 5. The main oxidation product Ta2O5 in the weld metal has the characteristics of high melting point and high hardness. When the Ta addition amount is low, the Ta2O5 formed has a small size and low distribution density, which has little effect on the elongation after fracture, but effectively improves the tensile strength, yield strength, hardness and impact absorption energy of the weld after welding. As the Ta addition amount increases, the size of Ta2O5 increases and the distribution density increases, and the tensile strength, yield strength, hardness and impact absorption energy of the weld are further improved. During the stretching process, large-sized particles of Ta2O5 are easily used as fracture induction points. Therefore, the elongation after fracture is further reduced as the size of Ta2O5 formed by excessive Ta addition increases and the distribution density increases.
[0075] In summary, CaF2-TiO2 melting flux is added to the flux-cored welding wire of the present invention, so that the weld welded by the flux-cored welding wire has good formability and excellent arc stability. At the same time, TiO2 may decompose at high temperature, increase the Ti and O content in the weld metal, and promote the formation of Ti-containing inclusions, which can effectively induce the nucleation of acicular ferrite. The introduction of a large amount of Ta increases the precipitation of MX-type carbides and has a significant dispersion strengthening effect, greatly improving the strength of the weld metal. At the same time, Ta has a high affinity with O and is very easy to form Ta2O5 during the welding process. This oxide has the characteristics of high melting point and high hardness, and can be used as an effective nucleation point for acicular ferrite. Ta is a ferrite stabilizing element. The addition of Ta increases the temperature of austenite to ferrite transformation in the weld, which is beneficial to enhance the phase transformation driving force of ferrite transformation and promote the nucleation of acicular ferrite on the surface of Ta2O5. As a result, the weld metal still maintains strength matching that of the base material and high low-temperature impact toughness under EGW ultra-large line energy heat input (for example: greater than 600kJ / cm), and the mechanical properties are much higher than the required values.
[0076] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A flux-cored welding wire, characterized in that: The invention comprises an outer skin and a core, wherein the core is filled inside the outer skin; the core is composed of the following components in mass percentage: C 0.48-0.78%, Al 0.72-0.84%, Si 1.50-1.62%, Mn 10.20-11.40%, Ni 2.10-2.46%, Ti 1.14-1.26%, Mo 1.08-1.14%, Ta 0.06-1.48%, CaF2-TiO2 smelting flux 5-7%, and Fe as the balance; The CaF2-TiO2 smelting flux in the flux core is prepared by a preparation method comprising the following steps: Mixing CaF2 and TiO2 and smelting at a temperature not lower than 1550° C. to obtain a smelting product; quenching the smelting product with water, calcining at 700-900° C. for 3-5 hours, crushing and sieving to obtain the CaF2-TiO2 smelting flux; In the CaF2-TiO2 smelting flux, the mass percentage of CaF2 is 25-60%, and the mass percentage of TiO2 is 40-75%.
2. The flux-cored welding wire according to claim 1, characterized in that: The particle size of the CaF2-TiO2 smelting flux is 10-40 meshes.
3. The flux-cored welding wire according to claim 1, characterized in that: The filling rate of the flux core in the flux cored welding wire is 20-30%.
4. The flux-cored welding wire according to claim 1, characterized in that: The outer skin is H08A steel.
5. The flux-cored welding wire according to claim 1, characterized in that: The particle size of the drug core is ≤80 meshes.
6. The flux-cored welding wire according to any one of claims 1 to 5, characterized in that: The flux-cored welding wire has a line energy of 400-800 kJ / cm during welding.
7. The method for preparing a flux-cored welding wire according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials of the flux core are mixed and filled into the outer skin, and then cold-bent, sealed, drawn and reduced in diameter to obtain the flux-cored welding wire.
8. Use of the flux-cored welding wire according to any one of claims 1 to 6 in the field of welding.
Citation Information
Patent Citations
Argon-filling-free backing welding rod for nickel-based alloys
CN111438463A
Flux-cored wire for gas shield arc welding, and manufacturing method of weld joint
JP2018192520A